Local Potential-Based Rural Development in Aceh Besar District, Indonesia - Mustaqim Mustaqim; Meki Herlon; Zulhamid Ridho; Ibnu Phonna; Riki Yulianda (Jurnal Ilmu Pendidikan dan Humaniora, 2025)
This study explores local potential-based rural development in Saree Village, Aceh Besar District, Indonesia. Saree holds significant promise as an agrotourism destination rooted in conservation and education. The village is endowed with rich natural assets, including Pocut Meurah Intan Grand Forest Park, Mount Seulawah Agam and Seulawah Inong, and the Saree Elephant Training Center, all of which support the development of sustainable ecotourism. These advantages are complemented by the presence of an Agro Techno Park and an integrated farming system producing key commodities such as avocados, red chilies, and tomatoes. This qualitative descriptive research employed field observations, interviews with local stakeholders, and literature reviews to identify and analyze the village’s local potentials. The Business Model Canvas (BMC) was applied as an analytical framework to map out the integration of local resources into tourism-based economic development.  Economically, over 65% of Saree's population depends on the agricultural sector, supported by training institutions such as Agro Saree Aceh that promote sustainable and technology-based farming. Collaborative efforts among local communities, village-owned enterprises (BUMG), government agencies, and the private sector play a crucial role in shaping Saree as an educational tourism village. The findings indicate that local resources can be effectively transformed into community-based tourism products that generate income, enhance local capacity, and preserve environmental sustainability. Key success factors include digital marketing strategies, human resource development, and infrastructure improvement.